ANALYSIS OF AIR POLLUTION LEVEL DUE TO EXHAUST GAS EMISSIONS FROM KRI IN THE KOARMADA B - Yudha Sukma Perdana; I Made Jiwa Astika; Adi Bandono (Indonesian Naval Technology College STTAL, 2021)
Exhaust gas from ships is a source of air pollution, which has a very detrimental impact on the environment and living things. Global warming, storms, drought, floods, melting of the north and south polar ice which causes sea levels to rise then causing tidal flooding, forest fires, and disruption of human health, are the impacts and dangers of air pollution. Exhaust gas emissions from KRI operations contribute to air pollution. Based on these conditions, the authors feel it is important to conduct research to determine the level of exhaust emissions so that they can be used as a reference for the Indonesian Navy's policy in supporting the Indonesian government's efforts to prevent air pollution. The research was conducted using a combination of quantitative and qualitative methods. The numerical analysis approach by calculating the value of KRI exhaust emissions is carried out then the results of the calculations are analyzed using a descriptive qualitative analysis approach. From the research results, it was found that 87.5% of KRI had exceeded the allowable exhaust gas emission limit, while only 12.5% ​​were still within the tolerance limit. Keywords: Exhaust Emission, Air Pollution